EVALUASI DANA DESA DALAM PENINGKATAN PEMBANGUNAN DESA DI DESA SUNGAI MULUK KECAMATAN MUARA PAPALIK KABUPATEN TANJUNG JABUNG BARAT - Piah, Lis; Heriberta; Nurjanah , Rahma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the characteristics of Sungai muluk Village and to evaluate the menagement of Village Funds in supporting rural development in Muara papalik Subdistrict, Tanjung Jabung Barat Regency. A descriptive qualitative approach was applied using APBDes data from 2020-2024, observation, and information from village offcials. The result show that the village population is largely composed of individuals in productive age groups, with agriculture as the primary livelihood. The Village Fund allocation increased annually, although the percentage growth varied. The funds were utilizes for infrastructure development and community empowerment programs, including red ginger powder production, livestock fattening, watermelon agro-tourism, and corn-based food security initiatives. However, several planned activities were not fully implemented, indication the need for improved planning and supervision. Overall, the village Fund has supported the progress of Sungai Muluk Village toward better development and greater self-realiance.